An extension of Horn's theorem for a space of locally integrable functions. (1992) - Henriquez, Hernan R.; Hernandez, Eduardo A.
Abstract : In this paper we extend the fixed point theorem of Horn's to the space of locally integrable functions from( − ∞, 0 ] into a Banach spaceX .